Geliat Gaya Hidup Halal Global: Peluang dan Tantangan - Mulyana, Rijal Assidiq (Sharia Economics Study Program Faculty of Islamic Economics and Business UIN Sunan Gunun, 2024)
The halal lifestyle is currently under scrutiny and experiencing massive growth not only in Indonesia but worldwide. It has evolved beyond being just a trend among contemporary societies to become a business and investment opportunity. The research is conducted through a qualitative approach, specifically a systematic literature review consisting of three stages: planning, conducting, and reporting. The research findings indicate that the halal lifestyle is not merely a modern way of living aligned with Islamic values but also has a futuristic dimension concerning the afterlife. It is expanding not only in Islamic countries or those with a Muslim majority but also in countries with Muslim minorities. The consumer base for the halal lifestyle is continuously growing, making it a promising investment and business opportunity. This growth is supported by seven key industries: halal food and beverage, Islamic fashion, Islamic media and recreation, Muslim-friendly tourism, halal pharmaceuticals, halal cosmetics, and the Islamic financial sector. However, the development of the halal lifestyle faces challenges, including: 1) Limited Islamic economic experts advising companies, 2) Not all products have halal labels, 3) Limited prevalence of halal certification, 4) Increasing Islamophobia in Europe and America, 5) Limited availability of halal raw materials, and 6) Narrow interpretation of halal, mainly focusing on food and beverages.